Self-assembled, hemin-functionalized peptide nanotubes: an innovative strategy for detecting glutathione and glucose molecules with peroxidase-like activity - Song Xiang; Xincheng Long; Qiuxia Tu; Jian Feng; Xiaohe Zhang; Guangwei Feng; Li Lei (Nano Convergence, 2023)
Abstract Accurately detecting dynamic changes in bioactive small molecules in real-time is very challenging. In this study, a hemin-based peptide assembly was rationally designed for the colorimetric detection of active small molecules. Hemin-functionalized peptide nanotubes were obtained through the direct incubation of hemin (hemin@PNTs) and peptide nanotubes (PNTs) or were coassembled with the heptapeptide Ac-KLVFFAL-NH2 via electrostatic, π–π stacking, and hydrophobic interactions (hemin-PNTs). This new substance is significant because it exhibits the benefits of both hemin and PNTs as well as some special qualities. First, hemin-PNTs exhibited higher intrinsic peroxidase-like activity, which, in the presence of H2O2, could catalyze the oxidation of the substrate 3,3',5,5'-tetramethylbenzidine (TMB) to yield a typical blue solution after 10 min at 25 ℃. Second, hemin-PNTs showed significantly higher activity than that of hemin, PNTs alone, or hemin@PNTs. Hemin-PNTs with a 20.0% hemin content may cooperate to improve catalytic activity. The catalytic activity was dependent on the reaction temperature, pH, reaction time, and H2O2 concentration. The nature of the TMB-catalyzed reaction may arise from the production of hydroxyl radicals. Fluorescence analysis was used to demonstrate the catalytic mechanism. According to this investigation, a new highly selective and sensitive colorimetric technique for detecting glutathione (GSH), L-cysteine, and glucose was established. The strategy demonstrated excellent sensitivity for GSH in the range of 1 to 30 μM with a 0.51 μM detection limit. Importantly, this glucose detection technique, which employs glucose oxidase and hemin-PNTs, is simple and inexpensive, with a 0.1 μM to 1.0 mM linear range and a 15.2 μM detection limit. Because of their low cost and high catalytic activity, hemin-PNTs are an excellent choice for biocatalysts in a diverse range of potential applications, including applications in clinical diagnostics, environmental chemistry, and biotechnology.